Costs and Evaluation of Vital and Essential Medicines for Internal Diseases Treatment, Purchased by Medical Organizations with the Funding from the System of Obligatory Medical Insurance in 2017 - O. M. Drapkina; A. V. Kontsevaya; M. V. Sura; R. N. Shepel; L. M. Zhamalov (Рациональная фармакотерапия в кардиологии, 2019)
Aim. To assess the cost and importance of the vital and essential medicines for the treatment of 12 groups of internal diseases purchased in 2017 by the «key» medical organizations in the subjects of Russian Federation with the funding from the system of compulsory medical insurance.Material and methods. We conducted the ABC and VEN analysis of the medications (according to the list of vital and essential medicines and clinical guidelines) treatment of 12 groups of internal diseases purchased in 2017 by the «key» medical organizations in the subjects of Russian Federation.Results. The study revealed that medical organizations show insufficient level of registration (less than 10% of the key medical organizations) regarding the medicines prescribed in the groups of diseases according to ICD-10, which complicates conducting large-scale research aimed at assessing the clinical and economical relevance of the provided treatment. Despite the fact that during the process of purchasing by medical organizations they are guided by the list of vital and essential medicines, the percent of expenses for the medicines which are not in the list, is still very high (more than 20%). At the same time in most of the groups being assessed, in the most expensive group A (80% of expenses) there were the medications not included in the list of vital and essential medicines. Conclusion. Assessment of correspondence between the medicines purchased by the medical organizations and those recommended by the guidelines is complicated due to the absence of clinical guidelines for the wide range of internal diseases. According to the preliminary assessments, the wide range of medications mentioned in clinical guidelines compared to the list of vital and essential medicines significantly broaden the number of essential medicines from the point of VEN-analysis.